CD3-positive B cells: a storage-dependent phenomenon - Nagel, Angela; Moebs, Christian; Raifer, Hartmann; Wiendl, Heinz; Hertl, Michael; Eming, Ruediger (PLoS ONE, 2014)
The majority of clinical studies requires extensive management of human specimen including e.g. overnight shipping of blood samples in order to convey the samples in a central laboratory or to simultaneously analyze large numbers of patients. Storage of blood samples for periods of time before in vitro/ex vivo testing is known to influence the antigen expression on the surface of lymphocytes. In this context, the present results show for the first time that the T cell antigen CD3 can be substantially detected on the surface of human B cells after ex vivo storage and that the degree of this phenomenon critically depends on temperature and duration after blood withdrawal. The appearance of CD3 on the B cell surface seems to be a result of contact-dependent antigen exchange between T and B lymphocytes and is not attributed to endogenous production by B cells. Since cellular subsets are often classified by phenotypic analyses, our results indicate that ex vivo cellular classification in peripheral blood might result in misleading interpretations. Therefore, in order to obtain results reflecting the in vivo situation, it is suggested to minimize times of ex vivo blood storage after isolation of PBMC. Moreover, to enable reproducibility of results between different research groups and multicenter studies, we would emphasize the necessity to specify and standardize the storage conditions, which might be the basis of particular findings.
EVALuna2:8253